Legal Protection for Buyers in Buying and Selling with Counterfeit Certificate Object - Putu Satria Fajar Purwanta; I Made Suwitra; Ketut Kasta Arya Wijaya (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
The lack of precision between the buyer and the land deed official is a factor in the emergence of the uncertainty of the law against the certificate issue. In addition, the seller also intentionally does not notify that there is a defect in the certificate that causes the buyer to suffer a loss. It needs the protection of the buyer acting in good faith so that in the future no longer appears dispute regarding the certificate of a double or false which is used as the object of buying and selling. This study aims to know the certainty of the law, the transfer of rights over the land and the form of the legal protection of the buyer acting in good faith in buying and selling with counterfeit certificate object. The method used in this study is normative legal research. In addition, the legal materials are obtained by using a literature study. The results of this study showed that the transfer of rights over the counterfeit certificate object causes legal uncertainty because there is a violation of article 1320 of the Civil Code, namely the agreement and skills that can be requested for cancellation, the form of the legal protection of the buyer acting in good faith in the form of protection repressive where such protection can be provided in the form of criminal sanctions, administrative and civil to the seller.